Botulinum toxin injection versus lateral internal sphincterotomy in the treatment of chronic anal fissure: a non-randomized controlled trial - (:unkn) unknown (BMC, 2004)
Background: Although lateral internal sphincterotomy is the gold-standard treatment for chronic anal fissure, intrasphincteric injection of botulinum toxin seems to be a reliable new option. The aim of this non-randomized study is to compare the effect of lateral internal sphincterotomy and botulinum toxin injection treatments on the outcome and reduction of anal sphincter pressures in patients with chronic anal fissure. Methods: Patients with chronic anal fissure were treated with either botulinum toxin injection or lateral internal sphincterotomy by their own choice. Maximal resting pressure and maximal squeeze pressure measurements were performed before and 2 weeks after treatments by anal manometry. Patients were followed for fissure relapse during 14 months. Results: Twenty-one consecutive outpatients with posterior chronic anal fissure were enrolled. Eleven patients underwent surgery and ten patients received botulinum toxin injection treatment. Before the treatment, anal pressures were found to be similar in both groups. After the treatment, the maximal resting pressures were reduced from 104+/-22 mmHg to 86+/-15 mmHg in the surgery group (p<0.05) and from 101 +/- 23 mmHg to 83 +/- 24 mmHg in the botulinum toxin group (p<0.05). The mean maximal squeeze pressures were reduced from 70+/-27 mmHg to 61+/-32 mmHg (p>0.05) in the surgery group, and from 117+/-62 mmHg to 76+/-34 (p<0.01) in the botulinum toxin group. The fissures were healed in 70 percent of patients in the botulinum group and 82 percent in the surgery group (p>0.05). There were no relapses during the 14 months of follow up. Conclusion: Lateral internal sphincterotomy and botulinum toxin injection treatments both seem to be equally effective in the treatment of chronic anal fissure.